Pengaruh Manfaat Utilitarian dan Manfaat Hedonis serta Status Sosial terhadap Keputusan Perpindahan Merek dari Televisi Kabel ke Netflix - Asty Almaida; Dedi Hariadi Saputra (Penerbit Goodwood, 2021)
Purpose: The purpose of this study is to determine the effect of utilitarian, hedonic, and social benefits on brand switching decisions from cable television to Netflix. Research Methodology: The data for this study were gathered via questionnaires and a review of the literature. Purposive sampling was used to collect data from 92 respondents who were active undergraduate students at the Faculty of Economics and Business Unhas in the 2016-2018 academic year and used the Video on Demand (VoD) Netflix service. Multiple regression analysis, F test (simultaneous), and T test are used in the analysis (partial). Results: The findings indicated that utilitarian benefits and social status had a positive and significant effect on brand switching decisions, whereas hedonic benefits had a negative and insignificant effect. Simultaneously, utilitarian, hedonic, and social benefits all have a positive and significant effect on brand switching decisions.